1998
DOI: 10.1128/iai.66.8.3562-3568.1998
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cytokine Production and Impaired Antimycobacterial Immunity in Protein-Malnourished Guinea Pigs

Abstract: Protein malnutrition leads to multiple detrimental alterations of host immune responses to mycobacterial infection. In this study, we demonstrated that splenocytes from low-protein (LP) guinea pigs vaccinated 6 weeks previously with attenuated Mycobacterium tuberculosis H37Ra failed to control the accumulation of virulentM. tuberculosis H37Rv in cocultured autologous peritoneal macrophages, despite the fact that they were able to control the accumulation of virulent tubercle bacilli in cocultured syngeneic per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 44 publications
3
42
0
Order By: Relevance
“…Thus, both mechanisms (i.e., increased resorption and decreased formation) are likely to impair implant osseointegration. In protein restriction-induced bone resorption, (11) bone resorptionstimulating cytokines, such as TNF-␣, (11,(31)(32)(33) or sex hormone deficiency could be implicated. (11) With the agerelated decline in renal function, blood pH slightly decreases, possibly in relation with excess dietary pro- tein.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, both mechanisms (i.e., increased resorption and decreased formation) are likely to impair implant osseointegration. In protein restriction-induced bone resorption, (11) bone resorptionstimulating cytokines, such as TNF-␣, (11,(31)(32)(33) or sex hormone deficiency could be implicated. (11) With the agerelated decline in renal function, blood pH slightly decreases, possibly in relation with excess dietary pro- tein.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the guinea pig serves as an ideal non‐primate model as it is hormonally and immunologically more similar to humans (13) than the rodent models. In particular, a guinea pig model for tuberculosis has been shown to have delayed type hypersensitivity and increased necrosis in lungs after Mycobacteria tuberculosis exposure similar to that seen in humans (14–16). Similarly, both genital and ocular infection of guinea pigs with the Chlamydia psittaci agent of guinea pig conjunctivitis results in a disease that parallels that seen in human and primates with respect to both infection course and pathologic response (17).…”
Section: Primers Used For Cloning Cd8α and Cd8βmentioning
confidence: 85%
“…In rats, moderate dietary PR during gestation impaired offspring thymocyte proliferation at birth and thymic and spleen lymphocyte proliferation at weaning (Calder and Yaqoob, 2000). Malnutrition decreased T cell function, cytokine production, and the ability of lymphocytes to respond appropriately to cytokines (Dai and McMurray, 1998). It was also reported that T lymphocytes from malnourished infants were shortlived and dysfunctional .…”
Section: Discussionmentioning
confidence: 99%